MgO-supported Ni-Sn Catalysts: Characterization and Catalytic Properties for Aqueous-phase Catalytic Reforming of Glycerol - Kiky Corneliasari Sembiring; Luthfiana Nurul Hidayati; Sudiyarmanto Sudiyarmanto; Fauzan Aulia; Asif Aunillah; Anis Kristiani (Jurnal Kimia Sains dan Aplikasi, 2021)
The aqueous phase reforming (APR) of glycerol into value-added products, including H2 and alkanes, is environmentally green. In this work, the conversion of glycerol into syngas was demonstrated using MgO-supported Ni-Sn catalysts. Ni species is known for its capability of converting glycerol, but the activity towards water gas shift (WGS) reaction has not been satisfied. Loading Ni-Sn onto MgO has increased the catalyst basicity, which promotes a positive effect in WGS reaction. A series of bimetallic catalysts, impregnated Ni-Sn on MgO support, was prepared with various Ni-Sn loading amounts. To better understand the behavior of prepared catalysts, they were evaluated physio-chemically through XRD, BET, and FTIR. The catalytic activity test was performed for APR in a continuous flow reactor with aqueous glycerol 10 v-% as a feedstock at a reaction temperature of 250°C. As a result, the maximum hydrogen selectivity was obtained at about 73 v-%.